The photochemistry and photobiology of vitamin B12 - Jones, Alex R (Photochemical & photobiological sciences, 2017)
Biologically active derivatives of vitamin B 12 are organometallic cobalt-corrinoid complexes crucial for the healthy function of humans, animals and microbes. Their role as cofactors to numerous, thermally-driven metabolic enzymes is well described, and varies depending on the nature of the upper axial ligand. This ligand also significantly influences the photophysics and photochemistry of B 12 . In this Perspective I will discuss the various aspects of B 12 photochemistry, from its dynamic spin chemistry to the considerable potential it has for biotechnology applications. Although for many years this photochemistry was thought to have no biological function, in recent years it has become apparent that B 12 photochemistry at very least has a role in light-dependent bacterial transcriptional regulation. I will provide an overview of what has been reported about B 12 photobiology to date, with particular emphasis on the mechanism of the transcriptional repressor, CarH, the subject of my Young Investigator Award Plenary Lecture at the European Society for Photobiology Congress 2015 in Aveiro, Portugal. This Perspective provides the first detailed overview of the photoresponse of vitamin B 12 and its derivatives, from the early, photophysical events to the burgeoning area of B 12 -dependent photobiology.